1986
DOI: 10.4049/jimmunol.136.5.1654
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of tubular basement membrane antigens in human kidney.

Abstract: Tubular basement membrane (TBM) was prepared from normal human kidneys and solubilized with various enzymes. Collagenase digestion released antigenic moieties from the TBM. All four anti-TBM antibodies we studied, three from patients with idiopathic tubulo-interstitial nephritis (TIN) and one from a renal allograft recipient, distinctively reacted with collagenase-digested (CD) TBM during enzyme-linked immunoassay and could discriminate among sera of normal controls or of other nephritis patients, including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“… 15 Some studies suggested that alternations in the proportion of D- and M-hexamers might prevent antibody binding due to the consequent lack of exposure of appropriate M-hexamers to GBM. 16 , 17 There is still a question as to how the immune response to α3(IV) was generated at first which might have involved some degradation of GBM. Noticeably, an experimental model has been delineated, wherein T cell-mediated anti-GBM damage is instigated in the absence of antibody deposition, which can provide a potential disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Some studies suggested that alternations in the proportion of D- and M-hexamers might prevent antibody binding due to the consequent lack of exposure of appropriate M-hexamers to GBM. 16 , 17 There is still a question as to how the immune response to α3(IV) was generated at first which might have involved some degradation of GBM. Noticeably, an experimental model has been delineated, wherein T cell-mediated anti-GBM damage is instigated in the absence of antibody deposition, which can provide a potential disease mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The basement membrane of the renal tubular cells is rarely exposed. Although immunogenic, pathological conditions related to formation of antitubular basement membrane antibodies are very rare with descriptions limited to case reports [ 2 , 3 ]. Anti-TBM antibody disease results from exposure of tubular proteins due to proximal tubular damage.…”
Section: Introductionmentioning
confidence: 99%